(Sub)alternating Imperia?: Law, Justice and Gender/Sexual Politics in Pakistan and Indonesia - Hamzić, Vanja (2011)
This paper seeks to highlight some of the meanings and shapes that the concepts of law and justice take amongst contemporary sexually and/or gender-variant Muslim subjectivities in Pakistan and Indonesia. In doing so, it argues for a new, critical approach in postcolonial theory, mindful, in the first place, of its past mishaps in analysing religious and cultural intersections with gender/sexual human experience.